Development of Responsibility Character Instruments for Junior High School Students - Suniawati, Ni Wayan Ari; Suarni, Ni Ketut; Dantes, Nyoman (Bisma The Journal of Counseling, 2021)
The aims of this study is to produce an instrument for measuring the character of responsibility in students. The type of research is research and development. In this study there are 10 steps that must be taken, namely: (1) setting the test objectives; (2) analysis of books and other learning resources, (3) making grids; (4) writing questions; (5) examine the questions (concept validation); (6) revision or improvement of questions; (7) limited test reproduction; (8) test trials (for empirical validation); (9) analysis of test results (validity test); and (10) assemble the questions into tests. The validation test was carried out by 5 counseling guidance experts consisting of 3 counseling guidance lecturers and 2 counseling guidance teachers. The results of CVI and CVR data analysis were +1, which means 45 statements were stated as relevant. Based on the empirical validation test with product moment, it is known that rhit > rtab so that 45 statements can be declared valid. Furthermore, the results of the reliability test using the cronbach alpha technique obtained r11 = 1.0 with a very high category.